2020
DOI: 10.1101/2020.04.21.20074757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitude, practice and perception regarding COVID-19 among students in Bangladesh: Survey in Rajshahi University

Abstract: 3 0

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
56
5
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 8 publications
17
56
5
6
Order By: Relevance
“…This poor knowledge could result from the low tertiary educational status and 'unstable' epidemiologic pattern of the virus. This agreed with what was documented in some Nigerian and Bangladesh studies [23][24][25][26] but opposed to what was reported in Egyptian and Chinese studies where a higher prevalence of good knowledge of COVID-19 was documented [17,19]. The higher prevalence recorded in these two studies could be due to the recruitment of seemingly educated online study populations.…”
Section: Discussionsupporting
confidence: 90%
“…This poor knowledge could result from the low tertiary educational status and 'unstable' epidemiologic pattern of the virus. This agreed with what was documented in some Nigerian and Bangladesh studies [23][24][25][26] but opposed to what was reported in Egyptian and Chinese studies where a higher prevalence of good knowledge of COVID-19 was documented [17,19]. The higher prevalence recorded in these two studies could be due to the recruitment of seemingly educated online study populations.…”
Section: Discussionsupporting
confidence: 90%
“…This poor knowledge could result from the low tertiary educational status and 'unstable' epidemiologic pattern of the virus. This agreed with what was documented in some Nigerian and Bangladesh studies [23][24][25][26] but opposed to what were reported in Egyptian and Chinese studies where a higher prevalence of good knowledge of COVID-19 was documented [17,19]. The higher prevalence recorded in these two studies could be due to the recruitment of seemingly educated online study populations.…”
Section: Discussionsupporting
confidence: 90%
“…In line with this, 96% of Chinese residents had mentioned fever, fatigue, dry cough, and myalgia as the main clinical symptoms of COVID-19 (16). Another study in Bangladesh also indicated that 98.7% of students believed that handwashing with soap and water followed by avoiding touching your nose, mouth and eyes with unwashed hands, the use of face mask/tissue when coughing or sneezing and wearing a clean surgical mask during their respiratory illness as the prevention methods for COVID-19 (17).…”
Section: Introductionmentioning
confidence: 99%